2014
DOI: 10.1111/jne.12163
|View full text |Cite
|
Sign up to set email alerts
|

Galanin‐Like Peptide (GALP) Neurone‐Specific Phosphoinositide 3‐Kinase Signalling Regulates GALP mRNA Levels in the Hypothalamus of Males and Luteinising Hormone Levels in Both Sexes

Abstract: Galanin-like peptide (GALP) neurons participate in the metabolic control of reproduction and are targets of insulin and leptin regulation. Phosphoinositide 3-kinase (PI3K) is common to the signaling pathways utilized by both insulin and leptin. Therefore, we investigated whether PI3K signaling in neurons expressing GALP plays a role in the transcriptional regulation of the GALP gene and in the metabolic control of luteinizing hormone (LH) release. To this end, we deleted PI3K catalytic subunits, p110α and p110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In the present study, we show that deletion of class IA PI3K catalytic subunit p110 α in adipose tissue results in delayed puberty onset and impaired fertility in males, with adults also showing hyperandrogenemia. The PI3K signaling pathway participates in the regulation of specific aspects of male reproductive function such as gonadotropin release [ 16 , 17 ], gonadal development [ 18 ], and spermatogenesis [ 19 ] acting on both the hypothalamic and the gonad level. To our knowledge, this is the first report to demonstrate that adipose tissue-specific disruption of PI3K signaling impairs male reproductive capacity, independent of a diet manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we show that deletion of class IA PI3K catalytic subunit p110 α in adipose tissue results in delayed puberty onset and impaired fertility in males, with adults also showing hyperandrogenemia. The PI3K signaling pathway participates in the regulation of specific aspects of male reproductive function such as gonadotropin release [ 16 , 17 ], gonadal development [ 18 ], and spermatogenesis [ 19 ] acting on both the hypothalamic and the gonad level. To our knowledge, this is the first report to demonstrate that adipose tissue-specific disruption of PI3K signaling impairs male reproductive capacity, independent of a diet manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter, PI3K mediates insulin effects on glucose uptake and lipolysis [ 13 15 ]. PI3K signaling also participates in the regulation of reproductive function; at the level of the hypothalamus, PI3K regulates the expression of neuropeptides important for fertility and gonadotropin release [ 16 , 17 ]; at the gonad level, PI3K signaling has been shown to regulate gametogenesis and spermatogenesis [ 18 , 19 ]. Class 1A PI3Ks are comprised of a catalytic subunit (p110 α , p110 β , or p110 δ ) bound to one of several regulatory subunits (collectively referred to as p85) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Grupe et al reported the association of GALP rs3745833 with increased risk for LOAD (Grupe et al, 2007 ). GALP is a neuropeptide, having important role in the central metabolic control of the reproductive axis (Aziz et al, 2014 ). It is a ligand in G-protein mediated signal transduction in CNS (Robinson et al, 2006 ).…”
Section: Genes and Molecular Pathways Implicated In MCI And Ad Riskmentioning
confidence: 99%
“…To generate mice in which the genes for the PI3K catalytic subunits p110␣ (Pik3ca) and p110␤ (Pik3cb) are deleted specifically in kisspeptin cells, double-floxed mice, p110␣ flx/flx / p110␤ flx/flx were mated with kisspeptin-IRES-CRE mice (58). Animals were screened for the presence of Cre and floxed p110␣ and p110␤ by PCR of isolated genomic tail DNA as described previously (3,55,58). The resulting F1 animals were then intercrossed to generate KissIC Ϫ p110␣ flx/flx / p110␤ flx/flx and KissIC ϩ p110␣ flx/flx /p110␤ flx/flx animals, referred to here as wild-type (WT) and kiss-p110␣/␤ knockout (KO), respectively.…”
Section: Generation Of Kiss-p110␣/␤-knockout Micementioning
confidence: 99%
“…Adult male mice of both genotypes were randomly assigned to one of three groups: intact sham operated (controls), Gdx ϩ V, or Gdx ϩ T. At the time of surgery, each animal received a subcutaneous Silastic capsule (1.02 ϫ 2.16 mm od) 5 mm in length filled with crystalline T or left empty (3,60). Adult female mice from each genotype were randomly assigned to one of three groups: intact sham operated (controls), Ovx ϩ V, or Ovx ϩ E 2.…”
Section: Gonadectomy and Steroid Hormone Replacementmentioning
confidence: 99%